2011
DOI: 10.1353/aad.2011.0006
|View full text |Cite
|
Sign up to set email alerts
|

The Modes of Communication Used by Children With Cochlear Implants and Role of Sign in Their Lives

Abstract: In a mixed-methods study, which included surveys of 247 parents and 151 teachers, the researchers investigated the modes of communication used by children with cochlear implants and the role of signed communication in the children's lives. Findings indicated that 15%–20% of the children in the parent surveys and approximately 30% of the children in the teacher surveys were using some form of signed communication. Qualitative findings from interviews with parents, teachers, and children with cochlear implants e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 47 publications
1
51
0
2
Order By: Relevance
“…Some of these studies examined influences on decision making related to a specific child characteristic (e.g., children using cochlear implants, described in Wheeler et al, 2009) or type of influence (e.g., culture, as in Borum, 2012). Other studies commented on caregiver decision making regarding communication mode (e.g., the use of sign by children with cochlear implants, as in Hyde & Punch, 2011) or sources of information that influence caregivers (e.g., the Internet, as in Porter & Edirippulige, 2007), although this was not the focus of the research.…”
mentioning
confidence: 99%
“…Some of these studies examined influences on decision making related to a specific child characteristic (e.g., children using cochlear implants, described in Wheeler et al, 2009) or type of influence (e.g., culture, as in Borum, 2012). Other studies commented on caregiver decision making regarding communication mode (e.g., the use of sign by children with cochlear implants, as in Hyde & Punch, 2011) or sources of information that influence caregivers (e.g., the Internet, as in Porter & Edirippulige, 2007), although this was not the focus of the research.…”
mentioning
confidence: 99%
“…Although there is some question as to whether these mixed utterances 14 inhibit children's optimal use of either language, the findings suggest that the separate assessment of languages does not demonstrate the linguistic complexity of which deaf children are capable 3.3 Research with children with cochlear implants Deaf children's changing bimodal and bilingual language practices have come under scrutiny in the specific context of cochlear implant (CI) research because of the early and increased access to the full range of speech sounds that CIs afford. The use of sign language changes following CI but nonetheless continues, particularly for those children with additional difficulties or where the outcomes of the CI are not as predicted (Hyde & Punch 2011). Studies of children's language show a general shift towards spoken language use but with the continued flexible use of sign language depending on individuals and contexts (Watson et al 2006).…”
Section: Research With Hearing Bimodal Bilingualsmentioning
confidence: 99%
“…Actual research about the veracity of the claims about negative impact of sign language for children with cochlear implants is sparse, however (HYDE;PUNCH, 2011;HAUSER, 2012). From a systematic literature review in which more than 1,500 international scientific references were studied, a Norwegian research team found that there were in fact no studies at all reflecting 'real' bilingual communication among children with cochlear implants, i.e.…”
Section: Children With Cochlear Implants -Some Words About Their Needmentioning
confidence: 99%
“…This will give them the basis for choosing what language works best in different situations, both at a young age and later in life (HOLMSTRÖM, 2013;HYDE;PUNCH, 2011). Such a free choice entails opportunities to communicate with other people and to function linguistically together with them, independent of their hearing status -opportunities that should be open to anyone.…”
Section: Children With Cochlear Implants -Some Words About Their Needmentioning
confidence: 99%